Intensity of cytosol expression of 8-OHdG in normal renal tubules is associated with the severity of renal fibrosis (Swiss Medical Weekly, 2011)
INTRODUCTION:It has been proposed thatreactive oxygen species play a role in renal fibrosis. 8-OHdG, a metabolite of oxidative damage to leukocyte DNA, has been identified as a marker of oxidative stress in patients with chronic renal failure. MATERIALS AND METHODS:Seventy-four patients following nephrectomy were retrospectively enrolled. Immunohistochemical analysis of the renal expression of 8-OHdG in the nephrectomised kidneys was performed and associations between renal expression of 8-OHdG and renal fibrosis were evaluated. RESULTS:Patients with higher interstitial fibrosis scores (IFS) and glomerular fibrosis scores (GFS) had significantly higher serum creatinine, lower estimated glomerular filtration rate (eGFR), increased percentage of chronic kidney disease (CKD) and urothelial cell carcinoma. The renal tissues with higher IFS had lower expressions of 8-OHdG in normal tubular cytoplasm (NTc) (35.7% vs. 64.3%, p = 0.011) and normal tubular nuclei (NTn) (28.6% vs. 71.4%, p = 0.023). Univariate analysis showed that IFS and GFS correlated with the NTc 8-OHdG expression and IFS negatively correlated with NTn 8-OHdG expression. Multivariate stepwise regression revealed that serum creatinine (r = 0.351 for IFS, p = 0.021; r = 0.563 for GFS, p